Learning Production, Formation of Internal Energy Human Body - Enjelika Hani Pamungkas; Anisa Kumala Dewi; Niken Kumalasari; Wahyu Kurniawati (Educare: Journal Educational and Multimedia, 2024)
The body needs energy as a source of power for all activities to move, humans need a certain amount of energy that comes from food. Energy is obtained from daily food which consists of various nutrients, especially carbohydrates and fat. The energy used to carry out activities in the human body is released through the process of burning substances/food. By measuring the amount of energy released, we can find out how much food is needed to produce energy in the human body. In elementary school students it is important to understand the body's need to produce energy. This learning is included in one of the science subjects. This research method is descriptive qualitative. The aim of this research is to find out the process of energy formation in the human body and what are the benefits of energy for the human body.